Manual de procedimentos administrativos de formalização de convênios e instrumentos congêneres: uma contribuição à coordenação de convênios da UFPB - Macêdo, Verônica Lins de Araújo (2017)
This technical work presents a Manual of Agreement Procedures and Related Instruments which the Federal University of Paraíba (Universidade Federal da Paraíba) can establish with public and private institutions. The end-result of the present study aims at guiding the adequate procedures according to the legislation so as to formalize the instruments which are needed to be established. Furthemore, the research took place in 5 (five) stages, from January to October 2017, in which data was collected, by means of research, about the internal norms of the Federal University of Paraíba (Universidade Federal da Paraíba) and the federal legislation concerning juridical instruments. Audit Reports and Judgements, issued by regulatory bodies, both internally and externally, were also researched, which presented findings and recommendations concerning the subject of the present study, as well as Dispatch Notes of the Attorney General’s Office (Advocacia Geral da União). Faced with this information, a proposal was elaborated, by means of a Manual, to serve as a guideline for those interested in the subject, as well as for managing offices and all the academic comunity at the Federal University of Paraíba (Universidade Federal da Paraíba) in the formalization of the juridical instrument.